Clinical trials for carotid stenosis revascularization and relation to methods of stenosis quantification. Issue 1 (December 2015) - Fox, Allan; Singh, Navneet
Abstract Severe carotid stenosis patients in the North American Symptomatic Carotid Endarterectomy Trial (NASCET) were shown to have a high risk of stroke and significant benefit from carotid endarterectomy. More than 20 years after the 1991 NASCET results for severe stenosis, there is a common claim to use the NASCET method to determine % carotid stenosis, but without following the details necessary to properly identify the group most benefitting from carotid endarterectomy. NASCET interpreted for loss of diameter of the cervical ICA, near occlusion, and didn't calculate % stenosis if present as it is fallacious. NASCET measured the distal ICA for well beyond the tapering ICA bulb where the ICA walls are parallel. The pitfalls of stenosis quantification and differences between methods are problems of the ratio's denominator, and may potentially be resolved by the use of absolute measurements for stenosis on CTA or MRA. Furthermore, trials evaluating vessel wall components including intraplaque hemorrhage such as CAIN may add to or replace degree of stenosis for the prediction of cerebrovascular outcomes.